2014 IEEE Conference on Computer Vision and Pattern Recognition 2014
DOI: 10.1109/cvpr.2014.206
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Scale Cost Aggregation for Stereo Matching

Abstract: Human beings process stereoscopic correspondence across multiple scales. However, this bio-inspiration is ignored by state-of-the-art cost aggregation methods for dense stereo correspondence. In this paper, a generic cross-scale cost aggregation framework is proposed to allow multi-scale interaction in cost aggregation. We firstly reformulate cost aggregation from a unified optimization perspective and show that different cost aggregation methods essentially differ in the choices of similarity kernels. Then, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(34 citation statements)
references
References 30 publications
(53 reference statements)
0
33
0
1
Order By: Relevance
“…They showed that higher-quality disparity maps can be obtained by adding a regularization term between the cost values of different scales, and that the computational time of cross-scale aggregation is not significantly greater than that of the original CVF [28]. This method [49] is similar to ours in terms of multi-scale cost-volume utilization, but its purpose is to improve the quality of the disparity maps, not to reduce the computational complexity. Recently, Zhan et al [48] proposed some techniques for local stereo matching methods to improve the accuracy: mask filtering as a pre-processing, an improved matching cost function, and multi-step disparity refinement as a post-processing.…”
Section: Cost Aggregation Methods For Labeling Problemsmentioning
confidence: 87%
See 2 more Smart Citations
“…They showed that higher-quality disparity maps can be obtained by adding a regularization term between the cost values of different scales, and that the computational time of cross-scale aggregation is not significantly greater than that of the original CVF [28]. This method [49] is similar to ours in terms of multi-scale cost-volume utilization, but its purpose is to improve the quality of the disparity maps, not to reduce the computational complexity. Recently, Zhan et al [48] proposed some techniques for local stereo matching methods to improve the accuracy: mask filtering as a pre-processing, an improved matching cost function, and multi-step disparity refinement as a post-processing.…”
Section: Cost Aggregation Methods For Labeling Problemsmentioning
confidence: 87%
“…Further, Lu et al [21] showed that higher-quality stereo matching results can be achieved by applying the CLMF instead of the GF for cost aggregation. Zhang et al [49] proposed a cross-scale cost aggregation algorithm based on CVF [28] for stereo matching. They showed that higher-quality disparity maps can be obtained by adding a regularization term between the cost values of different scales, and that the computational time of cross-scale aggregation is not significantly greater than that of the original CVF [28].…”
Section: Cost Aggregation Methods For Labeling Problemsmentioning
confidence: 99%
See 1 more Smart Citation
“…또한, 제안한 방법의 거리변환 지도 를 구하기 위해 Canny 경계 검출 방법으로 경계 영상 을 얻었다 [13] . 그림 9는 식 ( Conventional method [6] Proposed method…”
Section: 기존 방법과 제안한 방법의 성능을 실험하기 위해unclassified
“…For evaluation of the stereo vision test dataset we used the following popular stereo vision algorithms: SAD + texture thresholding (TX) & connected component filtering (CCF) (Konolige 1998), SGBM + TX & CCF (Hirschmüller 2008), census-based BM + TX & CCF (Humenberger et al 2010;Kadiofsky et al 2012), cost-volume filtering (CVF) & weighted median post processing filtering (WM) , PatchMatch (PM) & WM , and cross-scale cost aggregation using census and segmenttrees (SCAA) & WM (Zhang et al 2014), (Mei et al 2013). The resulting disparities of each stereo vision algorithm are compared to the GT disparities of the test dataset.…”
Section: Performance Evaluationmentioning
confidence: 99%